2014
DOI: 10.1378/chest.13-2688
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin-1 Predicts Disease Progression in Patients With Idiopathic Pulmonary Fibrosis

Abstract: BACKGROUND:The underlying mechanisms of idiopathic pulmonary fibrosis (IPF) are unknown. Th is progressive disease has high mortality rates, and current models for prediction of mortality have limited value in identifying which patients will progress. We previously showed that the glycoprotein fi bulin-1 is involved in enhanced proliferation and wound repair by mesenchymal cells and, thus, may contribute to lung fi brosis in IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 27 publications
3
44
0
Order By: Relevance
“…This extends other observations in which Fbln1 was increased in the serum of asthma (13) and IPF patients (15), suggesting that Fbln1 may be a biomarker and therapeutic target in respiratory diseases and other conditions involving remodeling and inflammation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This extends other observations in which Fbln1 was increased in the serum of asthma (13) and IPF patients (15), suggesting that Fbln1 may be a biomarker and therapeutic target in respiratory diseases and other conditions involving remodeling and inflammation.…”
Section: Discussionsupporting
confidence: 87%
“…Increased levels of Fbln1 occur in serum and bronchoalveolar lavage fluid (BALF) of asthma patients, and inhibition of Fbln1c expression by antisense oligonucleotide reduced the proliferation of ASM cells from these patients (13). In IPF, ECM proteins are increased in both plasma and lung tissue (15), and Fbln1c variant–specific peptide increases the proliferation of lung fibroblasts, the main producers of ECM, in COPD and IPF patients (14). Cytokines associated with lung diseases, such as TGF-β, that are known to induce ECM proteins (16) also stimulate Fbln1 production in ASM cells from COPD patients, further indicating roles for Fbln1 in airway remodeling (17).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research we have found that the level of fibulin-1 is elevated in the serum and bronchoalveolar lavage fluid of patients with asthma compared to people without asthma, and serum and tissue fibulin-1 levels are increased in the patients with IPF compared to those without lung diseases1724. Furthermore we have found that gene silencing of FBLN1C reduced cell proliferation and wound healing of ASM cells and reduced features of lung disease in a murine model17.…”
mentioning
confidence: 92%
“…Due to its established role in the pathophysiology of airway fibrosis in patients with chronic asthma, fibulin-1 was supposed to be involved in the mechanisms of fibrogenesis and progression of IPF through a dysregulated expression [79]. In a recent study, Jaffar et al [80] have shown that fibroblasts of IPF patients produce more fibulin-1. Serum and tissue levels of this protein were increased in IPF compared with controls and correlated negatively with lung function (FVC).…”
Section: Ecm Remodelling and Fibroproliferationmentioning
confidence: 99%